2015
DOI: 10.1080/23317000.2015.1128369
|View full text |Cite
|
Sign up to set email alerts
|

Voltage stability analysis of grid-connected wind farms with FACTS: Static and dynamic analysis

Abstract: Recently, analysis of some major blackouts and failures of power system shows that voltage instability problem has been one of the main reasons of these disturbances and network collapses. In this article, a systematic approach to voltage stability analysis using various techniques for the IEEE 14-bus case study is presented. Static analysis is used to analyze the voltage stability of the system under study, while the dynamic analysis is used to evaluate the performance of compensators. The static techniques u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The simulation results also showed that STATCOM provides better performance than SVC. In [36], static and dynamic voltage stability analyses of grid-tied wind farms incorporating FACTS devices were carried out. The static analysis was done using static techniques such as power flow, PV curve analysis, and QV modal analysis to examine the voltage stability of IEEE 14-bus test system while the dynamic analysis was performed to evaluate the performance of SVC and STATCOM during both normal and contingency conditions.…”
Section: Voltage Stability With Wind Energy Integration and Facts Appmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results also showed that STATCOM provides better performance than SVC. In [36], static and dynamic voltage stability analyses of grid-tied wind farms incorporating FACTS devices were carried out. The static analysis was done using static techniques such as power flow, PV curve analysis, and QV modal analysis to examine the voltage stability of IEEE 14-bus test system while the dynamic analysis was performed to evaluate the performance of SVC and STATCOM during both normal and contingency conditions.…”
Section: Voltage Stability With Wind Energy Integration and Facts Appmentioning
confidence: 99%
“…Since Wind Energy Conversion Systems constitute the largest variable renewable energy sources with large scale integration, several studies have been carried out to investigate voltage stability of power grids with high penetration of wind energy systems [ 1 , 9 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Three of the most-commonly investigated WECS are the Permanent Magnet Synchronous Generator (PMSG) based WECS, Doubly-Fed Induction Generator (DFIG) and Squirrel-Cage Induction Generator (SCIG).…”
Section: Review Of Facts Devices Applications For Voltage Stability Ementioning
confidence: 99%
“…Voltage is fully associated with reactive powerby assuming real power at every operating point is constant. Then the stability of the voltage can be calculated via the incremental relation between reactive power and voltage (Heetun, Abdel Aleem, & Zobaa, 2016). The reduced Jacobian matrix is given as:…”
Section: Modal Analysismentioning
confidence: 99%
“…X=ffalse(x,yfalse)0=gfalse(x,yfalse) The steady state equilibrium values ( x 0 y 0) of small disturbance in the dynamic system can be evaluated by setting the derivative in (1) to zero. Equations (1) and (2) are expressed as shown in (3) and (4) [34]. Further, by eliminating Δ y , the linearised state equation can be written as shown in (5) and (6).…”
Section: Dynamic Stability Analysismentioning
confidence: 99%